Study of acrylamide level in food from vending machines - Naceur Haouet; Simona Pistolese; Raffaella Branciari; David Ranucci; Maria Serena Altissimi (Italian Journal of Food Safety, 2016)
Acrylamide is a by-product of the Maillard reaction and is potentially carcinogenic to humans. It is found in a number of foods with higher concentrations in carbohydrate-rich foods and moderate levels of protein-rich foods such as meat, fish and seafood. Acrylamide levels in food distributed in vending machines placed in public areas of the city of Perugia were analysed by high-performance liquid chromatography. Samples included five different categories, depending on the characteristics of the products: i) potato chips; ii) salted bakery products; iii) biscuits and wafers; iv) sweet bakery products; v) sandwiches. A high variability in acrylamide level among different foods and within the same category was detected. Potato chips showed the highest amount of acrylamide (1781±637 μg/kg) followed by salted bakery products (211±245 μg/kg), biscuits and wafers (184±254 μg/kg), sweet bakery products (100±72 μg/kg) and sandwiches (42±10 μg/kg). In the potato chips and sandwiches categories, all of the samples revealed the presence of acrylamide, while different prevalence was registered in the other foods considered. The data of this study highlight the presence of acrylamide in different foods sold in vending machines and this data could be useful to understand the contribution of this type of consumption to human exposure to this compound.